2005
DOI: 10.1002/jso.20269
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative diagnosis of medullary thyroid carcinoma: Fine needle aspiration cytology as compared with serum calcitonin measurement

Abstract: Despite the higher sensitivity of serum CT measurement, as compared with FNAC to diagnose MTC (98% vs. 63%), only 9% of patients might have escaped to surgery based on FNAC results. However, indication for surgery based on suspicious FNAC may not alert the surgeon for the need of a TT and exploration of nodes at least in the central compartment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
91
1
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(106 citation statements)
references
References 35 publications
8
91
1
5
Order By: Relevance
“…More significant is that non-specific cytological features may wrongly suggest tumors other than MTC. These false negative diagnoses result in the failure to cytologically diagnose MTC, and lower cytological sensitivity for MTC (45,(47)(48)(49)(50)(51)(52)(53)(54)). An abstract reporting 14 samples (from 13 patients) that positively expressed the MTC gene expression signature in the Afirma GEC rare neoplasm cassettes found that all 14 were confirmed as MTC on histopathology (55).…”
Section: Rare Neoplasmsmentioning
confidence: 99%
“…More significant is that non-specific cytological features may wrongly suggest tumors other than MTC. These false negative diagnoses result in the failure to cytologically diagnose MTC, and lower cytological sensitivity for MTC (45,(47)(48)(49)(50)(51)(52)(53)(54)). An abstract reporting 14 samples (from 13 patients) that positively expressed the MTC gene expression signature in the Afirma GEC rare neoplasm cassettes found that all 14 were confirmed as MTC on histopathology (55).…”
Section: Rare Neoplasmsmentioning
confidence: 99%
“…In a comparison of 18 F-FDG, 18 F-DOPA, and 68 Ga-somatostatin analogue PET-CT in individuals with recurrent MTC, the metastatic lesion detection rates were 28%, 85%, and 20%, respectively. According to those data, 18 F-DOPA PET-CT seems to be the most useful method for detecting MTC recurrences in individuals with elevated serum calcitonin levels (174) (B). However, other studies showed no significant differences between PET 18 F-DOPA and 18 F-FDG in the same population (175) (B).…”
Section: (B)mentioning
confidence: 99%
“…The sensitivity of FNAB for diagnosing MTC in a thyroid nodule varies from 46.1-63% (17-19) (B). Although non-diagnostic, the FNAB findings in MTC are indicative of surgery in 99% of cases (17)(18)(19)) (B). Approximately 82% of MTC cases are correctly identified by FNAB, while 9% are false-negative results (18,19) (B).…”
Section: Recommendationmentioning
confidence: 99%
See 2 more Smart Citations